Discrimination of skyrmion chirality via spin–orbit and –transfer torques for logic operation - Yoshinobu Nakatani (Nature Portfolio, 2021)
Abstract Recently many works on magnetic memories and logic circuits, which use a magnetic skyrmion have been reported. Previously we micromagnetically simulated a method to switch a chirality of a magnetic skyrmion formed in a magnetic thin film by introducing a pulsed heat spot. In this paper, we propose a method to discriminate the chirality of a skyrmion in a branched nanowire by using spin–orbit torque (SOT) and spin-transfer torque (STT), and confirm the validity of the method by using simulation. The simulated results show that the motion changes depending on the chirality when additional SOT is applied on a skyrmion moving in a branch by STT. This method can be used as a fundamental building block for electrical detection in memory and logic devices using the chirality of skyrmions as a data bit in addition to the presence (and polarity) of the skyrmions as conventionally used, which can be lead to multiple-valued operation.